1998
DOI: 10.1007/pl00007029
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role for Jasmonic Acid in Adaptation of Barley Seedlings to Salinity Stress

Abstract: The changes caused by NaCl salinity and jasmonic acid (JA) treatment (8 days) on growth and photosynthesis of barley plants (Hordeum vulgare L., var. Alfa) have been studied. Gas exchange measurements and analysis of enzyme activities were used to study the reactions of photosynthesis to salinity and JA. Both 100 mM NaCl and 25 M JA treatment led to a noticeable decrease in both the initial slope of the curves representing net photosynthetic rate vs intercellular CO 2 concentration and the maximal rate of phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 38 publications
4
38
0
1
Order By: Relevance
“…The photosynthetic rate was increased by R. leguminosarum strain induced by the inducers NA and the combined MJ+NA at 0.6 dS m -1 treatment but the effect was reversed using MJ. This result confirmed the findings of Tsonev et al 20) and other researches [26][27] who reported that the use of MJ generally decreased photosynthesis, plant height and leaf area under non-salinity stress. At 3.0 dS m -1 , the photosynthetic rate increase over the control was 7.6 and 12.3%, respectively while at 6.0 dS m -1 salinity, the increase was 15.4 and 0.5%, respectively.…”
Section: Plant Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…The photosynthetic rate was increased by R. leguminosarum strain induced by the inducers NA and the combined MJ+NA at 0.6 dS m -1 treatment but the effect was reversed using MJ. This result confirmed the findings of Tsonev et al 20) and other researches [26][27] who reported that the use of MJ generally decreased photosynthesis, plant height and leaf area under non-salinity stress. At 3.0 dS m -1 , the photosynthetic rate increase over the control was 7.6 and 12.3%, respectively while at 6.0 dS m -1 salinity, the increase was 15.4 and 0.5%, respectively.…”
Section: Plant Growthsupporting
confidence: 92%
“…JA and MJ, a volatile derivative of JA, are also involved in salinity stress. For example, the application of JA and MJ diminished the inhibitory effect of high salinity on growth and photosynthesis of barley 20) . Little is known about nodulation, photosynthesis and growth of pea medicinal plants grown under salinity stress conditions, when inoculated with rhizobia pre-incubated with NA and MJ inducers.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this beneficial effect, ABA could have a limited effect since it could form conjugates and/or be degraded rapidly (Cutler and Krochko, 1999). JA has also been found to facilitate acclimation of crops such as barley and strawberry to saline conditions (Tsonev et al, 1998).…”
Section: Influencia Del áCido Abscísico Y Otros Fitorreguladores En Lmentioning
confidence: 99%
“…The intensive research in stress physiology revealed its role as a signaling or stress-modulating molecule against various environmental stresses. Currently, JA is receiving much attention due to its multifunctional defense properties in plants against several abiotic stresses, including salinity (Tsonev et al, 1998), drought (Creelman and Mullet, 1997), and herbicides (Kaya and Doganlar, 2016). However, studies of its role in plants under heavy metal stress are few (Chen et al, 2014), especially regarding the interactive effects of Cd and JA application on rapeseed oil.…”
Section: Introductionmentioning
confidence: 99%